The geography of abortion: Discourse, spatiality and mobility. (December 2022) - Calkin, Sydney; Freeman, Cordelia; Moore, Francesca
Abortion has historically been ignored in geography. Although bodies and pregnancy have been increasingly studied since the 1990s, a reticence around abortion remains. In recent years, however, this has begun to change. This article critically reviews how geographers and other scholars are now considering abortion and uses three conceptual lenses of discourse, spatiality and mobility to argue that abortion should be a mainstream topic of critical concern for geographers. Through these themes we show that geographical attention to abortion makes questions of space, power, and citizenship visible in new ways and, furthermore, in ways that are only recently possible.